CHORIOCARCINOMA AFTER NORMAL VAGINAL DELIVERY; A RARE ENTITY - Abbasi, Azizun Nisa; Fawad, Anisa; Islam, Ansa; Ismail, Ayesha; Ullah, Obaid (Journal of Ayub Medical College Abbottabad, 2019)
Choriocarcinoma is a malignant gestational trophoblastic neoplasm with rare postpartum presentation. Its manifestation after full term delivery is very rare with paucity of data reported from Pakistan. We received a patient in the postpartum period with symptoms of distant metastasis. She was diagnosed with choriocarcinoma based on our workup and was referred for chemotherapy after management. Now she is receiving follow-up care. Keywords: Choriocarcinoma; postpartum; gestational trophoblastic neoplasm; chemotherapy